Pengaruh Model Team Assisted Individually terhadap Kemampuan Kognitif pada Pembelajaran IPA di Kelas 5 Sekolah Dasar - Ayu Melinda Permatasari; Azmi Al Bahij (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This research is motivated by the low cognitive abilities of students in science learning in elementary schools, which is largely caused by conventional teaching methods that do not actively involve students. To overcome this problem, the Team Assisted Individually (TAI) learning model is used, which combines a cooperative approach and individual learning to improve the understanding of science concepts more effectively. The purpose of this study is to determine the effect of the TAI model on the cognitive abilities of fifth-grade students of SD Islam Baitul Salam Ciledug on natural phenomena material. This study uses a quantitative approach with a quasi-experimental design and a pretest-posttest control group design technique. The sample consists of two classes, namely the experimental class that uses the TAI model and the control class that uses conventional learning methods. The results of the study show that there is a significant increase in the cognitive learning outcomes of students who participate in learning with the TAI model compared to the conventional method. Therefore, this study is expected to provide an alternative effective learning model for teachers, as well as improve the quality of the process and student learning outcomes, especially in science learning.